GoFood Sebagai Saluran Pemasaran Digital: Pemberdayaan UMKM Kedai Arabian Shawarma Dalam Transformasi Digital Melalui Pendampingan Teknis - Afandi, Khoirunnisa; Arief, M. Habibullah (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
This community service program aimed to empower the culinary micro-business Kebab Arabian Shawarma DR Soebandi through digital transformation using the GoFood platform. The partner faced challenges in digital marketing, including low technical literacy, lack of digital presence, and ineffective sales strategies, resulting in limited market reach and low revenue (average 5–7 orders/day, Rp6–8 million/month). The intervention employed a hybrid method combining technical assistance (GoFood account setup, product optimization, QRIS integration) and knowledge transfer (digital marketing training, promotional strategies). Results showed significant improvements: a 45% increase in revenue (Rp12.3 million/month), 85% digital transaction adoption, and expanded customer reach (35% new customers via GoFood). The program’s novelty lies in its gender-inclusive approach, focusing on female entrepreneurs, and its holistic integration of technical and educational support. Outcomes included enhanced digital literacy, independent platform management, and sustainable business growth, demonstrating the effectiveness of structured mentoring in bridging the digital divide for MSMEs.